2022
DOI: 10.1186/s12909-022-03330-w
|View full text |Cite
|
Sign up to set email alerts
|

Medical undergraduates’ self-evaluation: before and after curriculum reform

Abstract: Background In 2013, Taiwan launched a curriculum reform—the 7-year undergraduate medical education program was shortened to 6 years. This study explored the evaluation results from students regarding the curriculum reform and investigated graduates’ perceptions regarding the curriculum organization of the two academic training programs affected by this curricular reform. Methods A cross-sectional survey was conducted from May 14 to June 12, 2019. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…According to previous research, we adopted the general competence eld advocated by the widely accepted Accreditation Committee for Graduate Medical Education (ACGME) to evaluate the improvement of the individual abilities of medical students. These abilities are considered necessary to become an excellent doctor [20,21]. The results showed that after nearly one year of course study, there was a signi cant difference in the improvement of personal ability between the two groups of students.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous research, we adopted the general competence eld advocated by the widely accepted Accreditation Committee for Graduate Medical Education (ACGME) to evaluate the improvement of the individual abilities of medical students. These abilities are considered necessary to become an excellent doctor [20,21]. The results showed that after nearly one year of course study, there was a signi cant difference in the improvement of personal ability between the two groups of students.…”
Section: Discussionmentioning
confidence: 99%
“…Hands-on laparoscopic experience has been shown to considerably boost students’ technical skills, enhance learning, maintain motivation, and increase interest in surgery as a future career [ 9 , 10 ]. However, medical students’ exposure to laparoscopy is predominantly confined to watching live camera streams during surgeries [ 11 ]. Opportunities to hone their laparoscopic skills are often constrained because of limited hands-on experiences in their current curricula [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hands-on laparoscopic experience has been shown to considerably boost students' technical skills, enhance learning, maintain motivation, and increase interest in surgery as a future career (9,10). However, medical students' exposure to laparoscopy is predominantly con ned to watching live camera streams during surgeries (11). Opportunities to hone their laparoscopic skills are often constrained because of limited hands-on experiences in their current curricula (12,13).…”
Section: Introductionmentioning
confidence: 99%